SpringerLink. - Skye Hardesty (Issues in Science and Technology Librarianship)
SpringerLink is an online collection of over :200 peer-reviewed journals and 25 book series published by Springer covering a variety of topics in the sciences, social sciences, and humanities. SpringerLink contains citation and abstract information back to volume : issue 1 for most titles (Springer is in the process of digitally converting the back issues of all its titles). In most cases, full-text access, based on individual or institutional subscriptions, is available back to 1996 for each "current" journal title subscription. For earlier coverage, subscribers must purchase the historical archive (1843-1996) at additional cost. SpringerLink is also the gateway for accessing the products Landolt-Börnstein, Springer eBooks collection, and Springer reference works. [ABSTRACT FROM AUTHOR]